2002
DOI: 10.1002/app.10944
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of carbon dioxide in polyethylene/titanium dioxide composite under high pressure and temperature

Abstract: Solubility of carbon dioxide (CO 2 ) in a lowdensity polyethylene (LDPE)/titanium dioxide (TiO 2 ) composite was measured using a magnetic suspension balance (MSB) at a temperature from 423 to 473 K and pressures up to 15 MPa. The effect of the TiO 2 concentration on the solubility is investigated by varying TiO 2 content in the range of 0 -20 wt %. Extending the Sanchez-Lacombe equation of state and its mixing rule for binary mixture, a scheme of calculating CO 2 solubility in composite from MSB data is devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 14 publications
0
41
0
Order By: Relevance
“…They also have extensively measured the solubilities of CO 2 and N 2 in PS, PVAC, PBS, and PPO/PS blends with a magnetic suspension balance (MSB), [17][18][19] while Areerat et al have utilized the MSB to evaluate the solubility of CO 2 in LDPE. 20 Wong et al 21 explored the solubility of CO 2 in PS and PVC using an electrobalance. In addition to the variety of experimental methods employed to achieve solubility measurements, various approaches have been applied to account for the buoyancy effect produced by the swollen volume of the polymer/gas mixture.…”
Section: Theory and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…They also have extensively measured the solubilities of CO 2 and N 2 in PS, PVAC, PBS, and PPO/PS blends with a magnetic suspension balance (MSB), [17][18][19] while Areerat et al have utilized the MSB to evaluate the solubility of CO 2 in LDPE. 20 Wong et al 21 explored the solubility of CO 2 in PS and PVC using an electrobalance. In addition to the variety of experimental methods employed to achieve solubility measurements, various approaches have been applied to account for the buoyancy effect produced by the swollen volume of the polymer/gas mixture.…”
Section: Theory and Backgroundmentioning
confidence: 99%
“…In addition to the variety of experimental methods employed to achieve solubility measurements, various approaches have been applied to account for the buoyancy effect produced by the swollen volume of the polymer/gas mixture. Most researchers have used the Sanchez-Lacombe (SL) equation of state (EOS), 15,[17][18][19][20] while Wong et al 21 have applied the partial volume theory to predict the swollen volume caused by the dissolution of gas in the polymer. Sato et al [17][18][19] had done a thorough study on the volume swelling of polymer/gas mixtures based on the SL EOS for the buoyancy effect compensation to get reliable solubility data.…”
Section: Theory and Backgroundmentioning
confidence: 99%
“…These authors illustrated that using PET samples, for which the plasticizing effect of absorption of CO 2 gas molecules is high enough to decrease the T g and thus to induce crystallization at ambient temperature. They nicely showed that the density of the sample crystallized with dissolved CO 2 was smaller (y0.003 g /cm 3 ) than that of a thermally crystallized sample having the same crystallinity level. This difference was attributed to the presence of crystallites that would hinder the relaxation of the structural volume when the polymer changes from the rubbery to the glassy state upon the release of the CO 2 molecules.…”
Section: Introductionmentioning
confidence: 74%
“…Chen et al [2] observed that gas absorption increases in the presence of fillers (CaCO 3 , talc) and suggested that a certain amount of gas accumulates inside the micro-pores at the polymer-filler interface which thus helps to nucleate cells during the foaming process. However, this hypothesis of an enhanced dissolution was not validated using a much more accurate measurement device: Areerat et al [3], using a magnetic suspension balance, determined the same solubility of carbon dioxide in polyethylene, whether the polymer was charged with titanium dioxide particles or not, which preclude then the existence of a gas-rich interface. Ramesh et al [4] developed a new model for bubble nucleation in a PS matrix containing polybutadiene rubber dispersed particles, based on pre-existing microvoids at the rubber/polymer interface-these microvoids would result from the thermal processing history of the polymer-which then will favour bubble nucleation at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…However, a large amount of fundamental data is needed to design and optimize these processing procedures. For example, in the foaming of polymers assisted by scCO 2 , the cell size and cell density are decided by the solubility of CO 2 in the polymer matrix [3]. Thus, it is very important to measure the fundamental data of CO 2 in polymers.…”
Section: Introductionmentioning
confidence: 99%